Collaborative Dialogue and action for home-based work issues in Indian slum settlements - Trivedi, Neeti; Tiwari, Reena (Curtin University, 2012)
The paper provides design solutions to overcome home based work issues for women in Indian slum settlements. Three home based industries in slum settlements of Ahmedabad in India are studied. Women working in three different trades are observed to understand the work process, space and ergonomic requirements. Problems in work conditions and space limitations and considerations are identified by speaking with women from these industries. Architectural solutions and product designs are proposed that take into consideration the work process, women's feedback and affordability. The ability and capacity of women to undertake the proposed solutions becomes yet another critical aspect for consideration.